Mapping Sea Level Rise Behavior in an Estuarine Delta System: A Case Study along the Shanghai Coast. (February 2018) - Cheng, H.Q.; Chen, J.Y.; Chen, Z.J.; Ruan, R.L.; Xu, G.Q.; Zeng, G.; Zhu, J.R.; Dai, Z.J.; Chen, X.Y.; Gu, S.H.; Zhang, X.L.; Wang, H.M.
Abstract: Sea level rise (SLR) is a major projected threat of climate change that is expected to affect developing coastal cities located in estuarine delta regions. Shanghai is one such city, being located in the Yangtze River Delta (YRD). It is difficult, however, for decision-makers to implement adaptation due to the uncertain causes, magnitudes, and timings of SLR behaviors. This paper attempts to map the causes and magnitudes of SLR behaviors on a decadal scale. We analyze the tidal level records from 11 tidal gauge stations and the corresponding bathymetry measurements around these stations since 1921. We identify three new SLR behaviors along the Shanghai coast due to anthropogenic geomorphologic changes (AGCs), besides the well-known eustatic sea level rise (ESLR), tectonic subsidence (TS), and urban land subsidence (ULS). The first new behavior is regional sea level rise (RSLR), which occurs as a result of land reclamation and deep waterway regulation. The second is regional sea level fall (RSLF), which occurs because the channel bed is eroded due to sediment supply decline in the river catchment. The last SLR behavior is local tidal datum rise (LTDR). Thus, we project that the magnitude of SLR for the Shanghai coast ranges from 10 cm to 16 cm from 2011 to 2030. Clarifying SLR behaviors is important to aid local decision-makers in planning structural and non-structural measures to combat escalating flood damage costs in an estuarine delta system; this field is full of future challenges.